2015
DOI: 10.1111/mec.13432
|View full text |Cite
|
Sign up to set email alerts
|

Complex patterns of cis‐regulatory polymorphisms in ebony underlie standing pigmentation variation in Drosophila melanogaster

Abstract: Pigmentation traits in adult Drosophila melanogaster were used in this study to investigate how phenotypic variations in continuous ecological traits can be maintained in a natural population. First, pigmentation variation in the adult female was measured at seven different body positions in 20 strains from the Drosophila melanogaster Genetic Reference Panel (DGRP) originating from a natural population in North Carolina. Next, to assess the contributions of cis-regulatory polymorphisms of the genes involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 65 publications
(180 reference statements)
1
47
0
Order By: Relevance
“…Table 1 shows the correlation coefficients between pigmentation traits quantified in Miyagi et al (2015) and two stressrelated phenotypes, starvation resistance and chill coma recovery time, from Ayroles et al (2009) and Mackay et al (2012). The results indicated a negative correlation between the % dark-pigmented area of the A4 abdominal segment and starvation resistance, which indicated that darker individuals are less resistant to starvation.…”
Section: Physiological Traits Associated With Pigmentationmentioning
confidence: 94%
See 4 more Smart Citations
“…Table 1 shows the correlation coefficients between pigmentation traits quantified in Miyagi et al (2015) and two stressrelated phenotypes, starvation resistance and chill coma recovery time, from Ayroles et al (2009) and Mackay et al (2012). The results indicated a negative correlation between the % dark-pigmented area of the A4 abdominal segment and starvation resistance, which indicated that darker individuals are less resistant to starvation.…”
Section: Physiological Traits Associated With Pigmentationmentioning
confidence: 94%
“…After the food mixture was sufficiently heated and stirred, ~15 ml was dispensed into a glass vial (diameter 30 mm, height 103 mm), which was then plugged by a cotton ball wrapped in a piece of cotton cloth. Data on the following DGRP strains (Ayroles et al, 2009;Mackay et al, 2012;Miyagi et al, 2015) were used for the association study: Temperature treatment Flies were allowed to lay eggs on the standard corn-meal fly medium in a glass vial at 25 °C for 1−2 days. After adult flies were removed, the vial was kept at 25 °C for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations